2008
DOI: 10.1016/s1008-1275(08)60067-x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality pattern according to autopsy findings among traffic accident victims in Yazd, Iran

Abstract: Training courses for emergency unit medical staff with regard to interpreting radiological findings of head and neck and high clinical suspicion for cervical spine injuries are essential to improve the quality of early hospital care and reduce the mortality and morbidity of traffic accident patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 19 publications
11
28
1
Order By: Relevance
“…A study found that dominant causes of death is bleeding, head trauma and multiple fractures which were more prevalent causes among car drivers, motorcycle drivers or passengers, and pedestrians, respectively (68) The studies in Tehran, Mashhad and Khorram Abad showed that motorcycle accidents commonly result in lower limb injuries as compared to injuries to other parts of the body (53, 69, 70). However, most of the deaths caused by motorcycle accidents were due to head injuries, as a result of lack of helmet (62, 65, 71, 72). A study in Isfahan showed that lack of helmet usage was responsible for head and face injuries among most of the victims (73).…”
Section: Resultsmentioning
confidence: 99%
“…A study found that dominant causes of death is bleeding, head trauma and multiple fractures which were more prevalent causes among car drivers, motorcycle drivers or passengers, and pedestrians, respectively (68) The studies in Tehran, Mashhad and Khorram Abad showed that motorcycle accidents commonly result in lower limb injuries as compared to injuries to other parts of the body (53, 69, 70). However, most of the deaths caused by motorcycle accidents were due to head injuries, as a result of lack of helmet (62, 65, 71, 72). A study in Isfahan showed that lack of helmet usage was responsible for head and face injuries among most of the victims (73).…”
Section: Resultsmentioning
confidence: 99%
“…In the Islamic Republic of Iran about 87.6% of road traffic injuries are head injuries (8,9) and, in view of the low quality of management after accidents (10,11), we should consider more seriously protective measures such as seat-belt use to reduce the severity of injuries and prevent deaths (12). According to a recent survey, seat-belt wearing was found to be the most important factor affecting road safety in the Islamic Republic of Iran (13).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, occupational accidents in the construction industry resulted in the deaths of about 17.29 workers out of 100,000 between 1980 and 1992 (8). Accidents in the transportation industry also represent a major cause of morbidity and mortality of youth worldwide; in developing countries such as Iran, there is a high rate of deaths due to accidents in the transport sector, at 25.8 deaths per 100,000 people, whereas in developed countries, this rate is 19.9 deaths (9,10).…”
mentioning
confidence: 99%